1997
DOI: 10.1152/ajpregu.1997.273.4.r1332
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of maternal deprivation on the corticosterone response to stress in rats

Abstract: Twenty-four hours of maternal deprivation result in activation of the infant rat’s adrenocortical axis. In the present study we examined the long-term effects of maternal deprivation on the corticosterone (Cort) response to stress. Pups were maternally deprived (Dep) on postnatal day( PND) 11 and tested immediately ( PND 12) or returned to their mothers and tested at later ages. Testing consisted of a time course of the Cort response to a saline injection (5, 15, 30, and 60 min). At PND 12, the response of Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 36 publications
4
39
0
1
Order By: Relevance
“…Previous studies have demonstrated that neonatal maternal separation, an animal model of a stressful experience in childhood, can permanently modify the characteristics of the hypothalamicpituitary-adrenal gland (HPA) axis in the offspring (Plotsky and Meaney, 1993;Suchecki and Tufik, 1997;van Oers et al, 1998;Liu et al, 2000). An elevation in the plasma glucocorticoids (corticosterone in rodents) level is known to be a consequence of the HPA axis activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that neonatal maternal separation, an animal model of a stressful experience in childhood, can permanently modify the characteristics of the hypothalamicpituitary-adrenal gland (HPA) axis in the offspring (Plotsky and Meaney, 1993;Suchecki and Tufik, 1997;van Oers et al, 1998;Liu et al, 2000). An elevation in the plasma glucocorticoids (corticosterone in rodents) level is known to be a consequence of the HPA axis activation.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the hypothalamicpituitary-adrenal gland (HPA) axis is implicated in the pathogenesis of eating disorders (Koo-Loeb et al, 2000;Putignano et al, 2001;Gluck et al, 2004). Neonatal maternal separation, an animal model of stressful experiences in childhood, can permanently modify the characteristics of HPA axis in the offspring (Plotsky and Meaney, 1993;Suchecki and Tufik, 1997;van Oers et al, 1998;Liu et al, 2000). Neuropeptide Y (NPY), the most potent orexic peptide known, stimulates feeding (Stanley and Leibowitz, 1985;Kalra et al, 1999;Schwartz et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Neonatal maternal separation (MS), an animal model of stressful experiences in childhood, can permanently modify the characteristics of HPA axis in the offspring. [5][6][7][8] Glucocorticoids, stress hormones released by activation of the HPA axis, are known to be involved in the regulation of energy balance, 9,10 and some of the central effects of glucocorticoids are believed to be mediated by hypothalamic neuropeptides. 11,12 It has been reported that experiences of repeated MS during pre-weaning period increase the hypothalamic level of neuropeptide Y (NPY) in rats later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve-day-old rats that have been deprived of their mothers for the previous 24 hr exhibit a pronounced ACTH (Suchecki, Mozaffarian, Gross, Rosenfeld, & Levine, 1993) and corticosteroid response to stress (Levine, Huchton, Wiener, & Rosenfeld, 1992;Suchecki & Tufik, 1997), indicating that mother-infant interactions are at least partly responsible for the regulation of the HPA axis in developing pups (Rosenfeld, Suchecki, & Levine, 1992). While the maternal factors that contribute to the SHRP have not been clearly identified, feeding and stroking of the anogenital region is known to play a role: Pups that have been deprived of their mothers for 24 hr, but cannula fed during that time, show an amelioration of the deprivation effect on the HPA response (van Oers, de Kloet, Whalen, & Levine, 1998).…”
mentioning
confidence: 99%